2019
DOI: 10.1007/s10654-018-00478-y
|View full text |Cite
|
Sign up to set email alerts
|

Vision loss and 12-year risk of dementia in older adults: the 3C cohort study

Abstract: Bordeaux 2 Victor Segalen and Sanofi-Aventis. The Fondation pour la Recherche Médicale funded the preparation and initiation of the study. The Three-City study is also supported by the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
61
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(72 citation statements)
references
References 48 publications
5
61
1
1
Order By: Relevance
“…Based on a retrospective cohort study that included 7,685 patients, Davies-Kershaw et al (2018) revealed that patients who rated their own vision as moderate were two times (HR 2.0, CI 95% 1.4-3.1) and those with very poor vision, which was comparable to being blind, four times (HR 4.0, CI 95% 2.6-6.1) more likely to have dementia compared to those without vision impairment. Furthermore, based on a population cohort of 7,736 initially healthy and non-dementia patients, Naël et al (2019) revealed that moderate to severe near-vision impairment was also associated with an increased risk of dementia in the first 4 years of follow-up (HR 2.0, CI 95% 1.2-3.3), but not when patients were followed for more than 4 years. Furthermore, self-reported vision impairment was associated with an increased risk of dementia within the time frame of 4 years (HR 1.5, CI 95% 1.1-2.0), but this association was no longer significant after adjusting for important baseline covariates, such as cognitive impairment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on a retrospective cohort study that included 7,685 patients, Davies-Kershaw et al (2018) revealed that patients who rated their own vision as moderate were two times (HR 2.0, CI 95% 1.4-3.1) and those with very poor vision, which was comparable to being blind, four times (HR 4.0, CI 95% 2.6-6.1) more likely to have dementia compared to those without vision impairment. Furthermore, based on a population cohort of 7,736 initially healthy and non-dementia patients, Naël et al (2019) revealed that moderate to severe near-vision impairment was also associated with an increased risk of dementia in the first 4 years of follow-up (HR 2.0, CI 95% 1.2-3.3), but not when patients were followed for more than 4 years. Furthermore, self-reported vision impairment was associated with an increased risk of dementia within the time frame of 4 years (HR 1.5, CI 95% 1.1-2.0), but this association was no longer significant after adjusting for important baseline covariates, such as cognitive impairment.…”
Section: Discussionmentioning
confidence: 99%
“…Based on a retrospective cohort study, Davies-Kershaw et al (2018) revealed that moderate and severe vision loss was significantly associated with an increased risk of dementia. However, despite this and other evidence (Reyes-Ortiz et al, 2005;Clemons et al, 2006;Pham et al, 2006;Rogers and Langa, 2010;Davies-Kershaw et al, 2018), longitudinal studies have shown inconclusive evidence concerning the association between vision loss and the risk of dementia (Lin et al, 2004;Reyes-Ortiz et al, 2005;Sloan et al, 2005;Valentijn et al, 2005;Fischer et al, 2016;Hong et al, 2016;Naël et al, 2019). Most studies have focused on the cognitive decline rather than on dementia, used varied diagnostic criteria, or have been based on a subjective rather than an objective assessment, using small sample sizes or cross-sectional data.…”
Section: Introductionmentioning
confidence: 99%
“…Hearing loss and vision loss have been associated with dementia in HIC (38)(39)(40)(41)(42), but evidence for these associations in Latin America or other LMIC is lacking. The current results suggest that eye problems, but not hearing problems, are associated with an increased risk of dementia in Cuban older adults, but only in the older age group.…”
Section: Health Factorsmentioning
confidence: 99%
“…Recent reviews highlighted that sensory deterioration such as vision and hearing loss can both contribute to or be a consequence of cognitive decline through both direct and indirect mechanisms [ 6 ]. For example, dementia-related cortical vision processing abnormalities may give rise to such a link [ 4 , 7 ], but visual problems have also been found to precede cognitive decline and increase the risk of dementia [ 5 , 8 , 9 ]. However, the mechanisms suggested for this association are being debated, including functional disability affecting engagement with cognitively stimulating activities [ 5 , 8 , 10 ] and interaction with depressive symptomology [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, dementia-related cortical vision processing abnormalities may give rise to such a link [ 4 , 7 ], but visual problems have also been found to precede cognitive decline and increase the risk of dementia [ 5 , 8 , 9 ]. However, the mechanisms suggested for this association are being debated, including functional disability affecting engagement with cognitively stimulating activities [ 5 , 8 , 10 ] and interaction with depressive symptomology [ 8 ]. Overall, it is suggested that addressing global sensory deterioration may significantly impact the quality of life for PWD and their caregivers [ 9 - 11 ], with some studies suggesting that routine sight-restoring treatments such as cataract surgery have the potential to modify the trajectory of cognitive decline [ 12 ] or increase gray matter volume [ 13 ].…”
Section: Introductionmentioning
confidence: 99%